Engineering detoxified pneumococcal pneumolysin derivative ΔA146PLY for self-biomineralization of calcium phosphate: Assessment of their protective efficacy in murine infection models. (February 2018) - Wu, Jingwen; Wu, Kaifeng; Xu, Wenchun; Yuan, Taixian; Wang, Xiaofang; Zhang, Jinghui; Min, Yajun; Yin, Yibing; Zhang, Xuemei
Abstract: Vaccine design ushered in the era of nanotechnology, as the vaccine is being developed toward particulate formulation. We have previously shown that the attenuated pneumolysin mutant (ΔA146PLY) was a safe and effective pneumococcal vaccine candidate. Here, to further optimize the formulation, we fused calcium phosphate (CaP) binding domains with ΔA146PLY so that the biocompatible CaP can mineralize with the protein automatically, allowing simple production of nanoparticle antigen during preparation. We fabricated four different nanoparticles, and then we compared the characteristics of different CaP-ΔA146PLY nanoparticles and demonstrated the influence of CaP binding domains on the size, shape and surface calcium content of the nanoparticles. It was found that these self-biomineralized CaP-ΔA146PLY nanoparticles varied in their capacity to induce BMDCs and splenocytes production of cytokines. We further demonstrated that, compared to free proteins, nanoparticle antigens induced more efficient humoral and cellular immune responses which was strong enough to protect mice from both pneumonia and sepsis infection. Also, the integration of CaP to protein has no significant impairment on body weight of animals, and subcutaneous injection of ΔA146PLY-peptides@CaP nanoparticles did not lead to permanent formation of nodules in the skin relative to Alum adjuvant formulated antigens. Together, our data sufficiently suggest that soluble ΔA146PLY vaccine candidate could be processed into nanoparticles by self-biomineralization of CaP, the immunogenicity of which could be efficiently improved by the CaP binding domains and biomineralization.